Improving Students Reading Ability Using SQ3R Method - Etika Ariyani Ariyani (Muhammadiyah University of Mataram, 2022)
this research aims to improve students reading comprehension by using SQ3R method. This research was a classroom action research and it was conducted in two cycle, each cycle consist of 3 meetings.